Elucidation of physio-chemical characterization of ultrasonic chemically demulsified crude oil - Wafaa, Kamil Mahmood (2014)
Formation of emulsions during oil production and processing is a costly problem, both in terms of chemicals used and production losses. It is necessary to separate the water completely from the crude oils before transporting to refinery. Traditional ways of breaking emulsions using heat and chemicals are disadvantageous from both economic and environmental perspectives. In this thesis, an alternative and multiple frequency energy potential of ultrasonic-assisted chemicals (environmental friendly) in demulsification of water-in-crude oil emulsions were utilized and investigated. Two types of crude oils were used namely; (Tapis and Miri crude oils). The study begun with some characterization studies to provide understanding of fundamental issues such as formation, formulation and breaking of emulsions by both chemicals and ultrasonic approaches. The aim was to obtain optimized operating conditions as well as fundamental understanding of water-in-oil stability, upon which further development of the demulsification process could be developed. The stability studies were carried out by analyzing operating conditions such as surfactant concentration, surfactant type, oil type, temperature and water-oil ratio (30-50%). For stability performance test, four emulsifiers were used namely; Triton X-100, Span 83, Cocamide DEA and SDDS. It was found that there exist a correlation between these factors and emulsion stability. Among these, emulsion stabilized by cocamide DEA was the best and followed by Span 83, SDDS and Triton X-100 respectively. For chemical emulsification performance test, five types of demulsifies with different functional groups were utilized; these are Hexylamine, Dioctylamine, Cocamine, Polyethylene Glycol, PEG 1000 and PEG 600. Among these; Hexylamine was found to be the best in separating water and oil from emulsions (88%) and followed by cocamine (81%), Dioctylamine (79%), PEG 1000 (76%) and PEG 600 (70%). For ultrasonic forces (3, 5, 7 and 9) applied for emulsion breaking, results were significantly enhanced the separation time and amount of water separated. Results showed that, ultrasonic power, 9 and Hexylamine (1.0%) in demulsifying the crude oil A stabilized by Span 83 with maximum water separation of 96% after 150 min. Also, and within the same operating conditions mentioned above, a maximum water separation up to 99% was achieved with crude oil B. The other investigated demulsifiers with ultrasonic force showed also high water separation percentages such as cocamine (1.0%) emulsifier with 91% and 93% for crude oils A and B emulsions respectively. The results obtained in this thesis have exposed the capability of ultrasonic-assisted chemicals technology in demulsification of W/O emulsions. Further works are nevertheless required to provide deeper understanding of the mechanisms involved to facilitate the development of an optimum system applicable to the industry